2016
DOI: 10.1007/s00114-016-1391-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of irritans mariner-like elements in the olive fruit fly Bactrocera oleae (Diptera: Tephritidae): evolutionary implications

Abstract: Genomic variation among species is commonly driven by transposable element (TE) invasion; thus, the pattern of TEs in a genome allows drawing an evolutionary history of the studied species. This paper reports in vitro and in silico detection and characterization of irritans mariner-like elements (MLEs) in the genome and transcriptome of Bactrocera oleae (Rossi) (Diptera: Tephritidae). Eleven irritans MLE sequences have been isolated in vitro using terminal inverted repeats (TIRs) as primers, and 215 have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Moreover, these gaps are fl anked by microhomologies. The association of microhomology with deletion breakpoints is reported in Mos1 (Brunet et al, 2002), mauritiana (Kharrat et al, 2015) and irritans elements (Ben Lazhar-Ajroud et al, 2016). These deletions do not occur randomly and could result from a host genome control, as well as from additional mechanisms, such as abortive gap repair (Rubin & Levy, 1997) and/or ectopic recombination between homologous short sequences leading to different deletion forms (Negoua et al, 2013;Kharrat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these gaps are fl anked by microhomologies. The association of microhomology with deletion breakpoints is reported in Mos1 (Brunet et al, 2002), mauritiana (Kharrat et al, 2015) and irritans elements (Ben Lazhar-Ajroud et al, 2016). These deletions do not occur randomly and could result from a host genome control, as well as from additional mechanisms, such as abortive gap repair (Rubin & Levy, 1997) and/or ectopic recombination between homologous short sequences leading to different deletion forms (Negoua et al, 2013;Kharrat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Class I elements, also known as retrotransposons, transpose via an RNA intermediate according to the "copy and paste" model. Class II elements, also named transposons move via a DNA intermediate according to the The identifi ed MLEs are mostly inactive owing to mutations affecting different parts of the elements and it has also been shown that many defective copies contain internal deletions that occur non randomly as ascertained by small direct repeats (SDRs) called microhomologies bordering deletion break points (BPs) (Brunet et al, 2002;Kharrat et al, 2015;Ben Lazhar-Ajroud et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies carried on ants highlighted a vertical transmission with differential evolutionary success and spread into different genomes during species-separation processes (Sanllorente et al, 2020). Other studies have revealed the establishment of irritans D r a f t subfamily elements in closely related Bactrocera species originating from the expansion from a common ancestor (Ben Lazhar-Ajroud et al, 2016) .…”
Section: In Vitro Search For Mauritiana-like Elementsmentioning
confidence: 81%
“…More interestingly, some deletions were found to cover the same positions in both Mayetiola species. This could be a mechanism contributing to defective MLEs or element decay as described in the irritans subfamily (Ben Amara et al, 2017, Ben Lazhar-Ajroud et al, 2016. Furthermore, Desmar1, MauCons1 and MauCons2-like elements exhibited high sequence identity between M. destructor and M. hordei which may indicate an eventual vertical inheritance of these MLEs from an intermediate common ancestor.…”
Section: In Vitro Search For Mauritiana-like Elementsmentioning
confidence: 92%
See 1 more Smart Citation